GEOECONOMIC IMPLICATIONS OF INDONESIA’S B50 BIODIESEL PROGRAM ON GLOBAL BIOFUEL SUPPLY CHAINS - Syhilla Putri Nadia; Muhammad Badaruddin (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2025)
The global biodiesel market is on the verge of significant disruptions due to Indonesia’s implementation of the B50 biodiesel program, which mandates a 50% biodiesel blend in the nation’s transportation fuel by 2026. This research explores the potential impacts of the B50 program on global biodiesel trade, production, and consumption. This qualitative research explores the potential global disruptions in the biodiesel market induced by Indonesia’s B50 biodiesel program. The findings suggest that Indonesia’s B50 program could lead to shifts in global trade flows, affecting both traditional fossil fuel markets and emerging green energy sectors. The study concludes with recommendations for industry stakeholders to mitigate risks and leverage new opportunities in this evolving landscape.